2020
DOI: 10.3389/fnins.2020.582934
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Glial Gap Junction Proteins Cx43, Cx30, and Cx47 in the 5XFAD Model of Alzheimer’s Disease

Abstract: Glial gap junction proteins, called connexins (Cxs), form gap junctions in the central nervous system (CNS) to allow the bidirectional cytosolic exchange of molecules between adjacent cells. Their involvement in inheritable diseases and the use of experimental animal models that closely mimic such diseases revealed the critical role of glial GJs in myelination and homeostasis. Cxs are also implicated in acquired demyelinating disorders, such as Multiple Sclerosis (MS) and Alzheimer's disease (AD). Animal and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 105 publications
4
18
1
Order By: Relevance
“…Also, the involvement of oligodendrocyte-specific connexins such as connexin-29 (CX29 or Gjc3), connexin-32 (CX32 or Gjb1) or connexin-47 (CX47 or Gjc2) in a manner similar to CX43 in astrocytes cannot be ruled out (179). A study showed a downregulation of oligodendrocytic CX47 in an AD model, contrasting with the increase of CX43 observed in astrocytes (180). The authors stipulate that such modification could favor astrocyte-astrocyte connection at the expense of astrocyte-oligodendrocyte communication, contributing to oligodendrocyte function impairment.…”
Section: Oligodendrocytesmentioning
confidence: 99%
“…Also, the involvement of oligodendrocyte-specific connexins such as connexin-29 (CX29 or Gjc3), connexin-32 (CX32 or Gjb1) or connexin-47 (CX47 or Gjc2) in a manner similar to CX43 in astrocytes cannot be ruled out (179). A study showed a downregulation of oligodendrocytic CX47 in an AD model, contrasting with the increase of CX43 observed in astrocytes (180). The authors stipulate that such modification could favor astrocyte-astrocyte connection at the expense of astrocyte-oligodendrocyte communication, contributing to oligodendrocyte function impairment.…”
Section: Oligodendrocytesmentioning
confidence: 99%
“…Cx43 and Cx30 normally function as GJCs, as was repeatedly shown by experiments in acute brain slices from knockout mice, including the astrocytic Cx43 conditional knockout mice (hGFAP-cre:Cx43 f l/fl ), the Cx30 knockout mice (Dere et al, 2003;Theis et al, 2003), and the double KO mice (hGFAPcre:Cx43 f l/fl :Cx30 KO) (Wallraff et al, 2006;Rouach et al, 2008;Pannasch et al, 2011;Roux et al, 2011). The expression levels of these two Cxs in astrocytes varies in different brain regions (Batter et al, 1992;Nadarajah et al, 1996;Nagy et al, 1999), and can be changed in neurodegenerative diseases, such as AD (Mei et al, 2010;Yi et al, 2016;Angeli et al, 2020). Additionally, Cx26 has also been detected in certain astrocytes to a lesser extent (Altevogt and Paul, 2004;Lynn et al, 2011;Nagy et al, 2011).…”
Section: Connexin Expression and Function In Astrocytesmentioning
confidence: 81%
“…Twenty years ago, Nagy and colleagues have firstly demonstrated that astrocyte Cx43 protein levels are increased in the brain tissue of AD patients, especially around the Aβ plaques (Nagy et al, 1995), which has been repeatedly confirmed (Kajiwara et al, 2018), and is also found in the APP/PS1 mouse model (Mei et al, 2010;Yi et al, 2016). However, a recent study showed that the mRNA level of Cx43 is decreased in the cortex and thalamus area of another mouse model of AD, 5xFAD mice, albeit the increased protein levels (Angeli et al, 2020). Treatment of Aβ 25−35 on primary astrocytes also results in a similar negative correlation between Cx43 mRNA and protein levels (Maulik et al, 2020).…”
Section: Astroglial Connexins In Admentioning
confidence: 98%
“…Several studies have proposed that connexin 43 (Cx43) in a hemichannel function mediates the Aβ peptide induction of ATP release from astrocytes. Thus, Cx43 is upregulated in AD mouse models and AD human brains [149][150][151][152]. Moreover, amyloid exposure triggers the increased expression of Cx43 both in vitro and in vivo AD models [82,153,154].…”
Section: Altered Atp Release From Astrocytes In Admentioning
confidence: 98%